Organizational Culture and Ethical Blind Spots in Managerial Accounting - Rely, Gilbert (Institut Bisnis dan Informatika Kesatuan, 2025)
In recent years, ethical concerns in managerial accounting have become more prominent, especially in light of corporate scandals. While traditional ethics frameworks emphasize individual responsibility and legal compliance, they often overlook how organizational culture shapes ethical decision-making. One crucial but often neglected factor is the presence of ethical blind spots, moral oversights influenced by cognitive biases and cultural norms within organizations. This study explores how such blind spots emerge and persist in managerial accounting, using a qualitative multiple-case approach. Interviews with managerial accountants and financial controllers from three mid-sized manufacturing firms revealed patterns of ethical reasoning shaped by internal culture. Findings suggest that organizations focused heavily on performance targets and rule compliance, while discouraging ethical dialogue, are especially prone to ethical blind spots. Concepts like ethical fading and organizational silence explain how unethical behavior can become normalized over time, even among well-meaning professionals. These moral lapses are not merely personal shortcomings but reflect deeper cultural dynamics. Addressing them requires more than strict rules; it involves cultivating a culture that promotes ethical reflection, open communication, and psychological safety. The study highlights the need for ethical culture assessments and calls for ethics training to be embedded in accounting education to foster long-term integrity and resilience within organizations.